Development of a design methodology for transport aircraft variable camber flaps suitable for cruise and low-speed operations - Ammoo, M. S. (Cranfield University, 2003)
This thesis describes the development of a generic design methodology for variable camber flap systems for transport aircraft, intended to be used for cruise and low-speed operations. The methodology was structured after several revisions were performed on conventional high-lift device design methodologies for existing transport aircraft. The definition and detail explanations are given at every phase of the methodology. A case study was performed in order to give an example of the implementation of the methodology where a transport aircraft called A TRA, a design study from previous PhD report, was taken as a model. Experimental work could not be performed, due to budget constraints, so the case study was only carried out using computer-based analyses. Software packages such as MSES-code (a Computational Fluid Dynamic software), CATIA and PATRANINASTRAN were used for this case study to analyse aerodynamic characteristics, layout as well as simulation and structure analyses respectively. The results obtained showed that it was practically feasible to deploy such a high-lift device to transport aircraft when the effect from aerodynamic loads gave minimum effect on structural deformation. The deflections of the flap as well as spoilers under critical loads were below the allowable limits, which had a minimal effect due to the additional lift force generated from the movable surfaces.